Pengaruh Arus Pengelasan Smaw pada Dissimilar Logam Stainless Steel 201 dan Baja 1040 Terhadap Sifat Mekanik dan Struktur Mikro: The Effect of Smaw Welding Current on The Mechanical Properties and Microstructure of Dissimilar Metals Stainless Steel 201 and Aisi 1040 Steel - Hadi, Qomarul; Matondang, Ifsya Ussalam; Zamheri, Ahamad (Journal of Engineering Science and Technology Applications, 2025)
The advancement of welding technology plays a crucial role in industrial development, especially in dissimilar metal welding, such as joining stainless steel 201 and carbon steel 1040. This type of welding often results in reduced mechanical properties at the joint due to differences in composition and physical characteristics. This study aims to investigate the effect of welding current variations on the tensile strength, hardness, and microstructure of dissimilar metal joints between stainless steel 201 and AISI 1040 steel. The welding method used is Shielded Metal Arc Welding (SMAW) with current settings of 85A, 90A, 95A, and 100A. Tests performed include tensile testing (ASTM E8M), hardness testing (JIS B 7725), composition analysis, and metallographic examination (ASTM E407-07). The results show that 95A is the most optimal current, producing the highest tensile strength and hardness values, particularly in the Heat Affected Zone (HAZ). Lower currents (85A and 90A) lead to insufficient penetration and fusion, a current of 100A generates the highest heat among all tested values. Composition analysis shows that stainless steel 201 primarily contains Fe, Cr, and Mn, while AISI 1040 is mostly composed of Fe. Variations in welding current also affect the microstructure, with the formation of phases such as widmanstätten ferrite and acicular ferrite, which significantly influence the mechanical properties of the welded joint.